ChemInform Abstract: Synthesis of Heteroarylogous 1H‐Indole‐3‐carboxamidines via a Three‐Component Interrupted Ugi Reaction. Issue 27 (18th June 2015) - La Spisa, Fabio; Meneghetti, Fiorella; Pozzi, Beatrice; Tron, Gian Cesare
Abstract The novel one‐pot multicomponent reaction is based on the reaction of N‐alkyl‐N‐(1H‐indol‐2‐ylmethyl)amines, with various carbonyl compounds, such as aldehydes including formaldehyde or cyclohexenone, and variously functionalized isocyanides.